Postwar Identity in the Making: Hidden Children in Volos (Greece) - Hantzaroula, Pothiti (Historein, 2019)
The high percentage of Jewish Holocaust survivors from Volos, compared to the devastating death rate in the rest of Greece, makes the city a case of its own. Scholars have analysed the factors that contributed to the survival rate of 74 percent of Volos’ Jewish population and dealt with survivors’ struggles to rebuild their lives after the Shoah. Yet, less attention has been paid to the construction of the memory of survivors, its complex reworking and its importance in shaping the lives and identities of communities. The study of the “exceptional” case of Volos through a microhistorical approach offers an opportunity to understand the variety, as well as the commonalities, of experiences of survivors among various communities in postwar Greece. Thus, questions such as postwar reintegration in the city, relations with the Christian population, the role of antisemitism in shaping postwar identities, and mixed marriages can be better understood when situated in a comparative perspective. The persistence of antisemitism in Volos against a highly assimilated community shows that there are no easy equations, either between survival and assimilation or between help by non-Jewish locals and a lack of antisemitism. By focusing on child survivors that went into hiding during the Shoah and by exploring the mutual relations and perceptions between the non-Jewish and Jewish population, the article aims to understand the ways in which such relationships and perceptions shaped postwar Jewish identities.